Influence of the type of occupation on osteoarthritis of the knee in men: The Korean National Health and Nutrition Examination Survey 2010‐2012. Issue 1 (21st January 2019) - Kwon, Sara; Kim, Won; Yang, Seoyon; Choi, Kyoung Hyo
Abstract: Objectives: We investigated the influence of different types of lifetime occupation on knee osteoarthritis (OA) and pain based on a nationwide survey in Korea. Methods: We conducted a cross‐sectional study using Korea National Health and Nutrition Examination Survey (KNHANES) from 2010 to 2012. Men ≥50 years old were divided into four occupational groups: white‐collar (WC) workers, pink‐collar (PC) workers, blue‐collar (BC) workers, and agribusiness and low‐level (AL) workers. The risks for knee OA and pain development according to occupation were compared to the risks in WC workers, using multiple logistic regression analyses. Results: Different occupations were associated with different levels of risk for knee OA and knee pain. The risk for knee OA was higher in BC workers and in AL workers than in WC workers, in order of higher risk. The risk for severe knee OA was likewise higher in AL workers and in BC workers, in order of higher risk. The risk for chronic knee pain was higher in AL workers, BC workers, and PC workers, in order of higher risk. The risk for moderate to severe chronic knee pain was higher in AL workers and BC workers, in order of higher risk. Conclusions: The results suggest that occupation might affect the development of knee OA and presence of chronic knee pain in men ≥50 years old. WC workers are least affected by knee OA and chronic knee pain, and AL and BC workers are at clearly higher risk for knee OA and chronic knee pain.